2008
DOI: 10.1063/1.2998521
|View full text |Cite
|
Sign up to set email alerts
|

Polymer induced condensation of DNA supercoils

Abstract: Macromolecular crowding is thought to be a significant factor driving DNA condensation in prokaryotic cells. Whereas DNA in prokaryotes is supercoiled, studies on crowding-induced DNA condensation have so far focused on linear DNA. Here we compare DNA condensation by poly͑ethylene oxide͒ for supercoiled and linearized pUC18 plasmid DNA. It is found that supercoiling has only a limited influence on the critical amount of PEO needed to condense plasmid DNA. In order to pack DNA supercoils in condensates, it seem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…We are not aware though of earlier numerical simulation studies, investigating the effect of topological exclusion by following the equilibration of systems composed of many supercoiled DNA molecules interacting with each other. Earlier numerical approaches to study the effect of crowding on supercoiled DNA molecules were based on simulations of individual molecules subject to potentials mimicking crowding by other molecules such as nematic and depletion attraction potentials ( 60 ). However, setting the strength of these potentials is currently somewhat arbitrary as we still lack sufficient understanding of phenomena happening in solutions of supercoiled DNA at given elevated concentration and at given supercoiling density.…”
Section: Discussionmentioning
confidence: 99%
“…We are not aware though of earlier numerical simulation studies, investigating the effect of topological exclusion by following the equilibration of systems composed of many supercoiled DNA molecules interacting with each other. Earlier numerical approaches to study the effect of crowding on supercoiled DNA molecules were based on simulations of individual molecules subject to potentials mimicking crowding by other molecules such as nematic and depletion attraction potentials ( 60 ). However, setting the strength of these potentials is currently somewhat arbitrary as we still lack sufficient understanding of phenomena happening in solutions of supercoiled DNA at given elevated concentration and at given supercoiling density.…”
Section: Discussionmentioning
confidence: 99%
“…219,220 Large DNA molecules, such as calf thymus DNA, bacterial DNAs, bacteriophage DNAs, and supercoiled and linearized plasmid DNAs, are also compacted by the addition of PEG (MW = 2 × 10 4 ) or PEO (polyethylene oxide; MW = 7.5 × 10 3 or 2 × 10 4 ). 221,222 The DNA compaction affects the transcriptional activity, and the transcription is completely inhibited after adding PEG. 223 It was proposed that the transition to the compact structure induced by environmental factors could play an essential role in regulating stable on−off switching of genes in cells.…”
Section: Dna Condensationmentioning
confidence: 99%
“…DNA exists as a compact structure inside bacteriophage heads, bacteria nucleoids, and eukaryotic nuclei. , The DNA compaction is induced by the condensation of DNA molecules mediated by the binding of counterions. The compaction occurs in vitro with high concentrations of multivalent ions that effectively neutralize the charge of condensed DNA. , Large DNA molecules, such as calf thymus DNA, bacterial DNAs, bacteriophage DNAs, and supercoiled and linearized plasmid DNAs, are also compacted by the addition of PEG (MW = 2 × 10 4 ) or PEO (polyethylene oxide; MW = 7.5 × 10 3 or 2 × 10 4 ). , The DNA compaction affects the transcriptional activity, and the transcription is completely inhibited after adding PEG . It was proposed that the transition to the compact structure induced by environmental factors could play an essential role in regulating stable on–off switching of genes in cells .…”
Section: Cosolute Effects On the Structures And Interactions Of Nucle...mentioning
confidence: 99%
“…Still, relaxation of supercoiling by inhibition of the gyrase activity induces only a limited increase in the size of the nucleoid of E. coli cells, typically from 5% to 40% in volume [78], while an increase of at least 400% would be needed for the nucleoid to expand through the whole cell. Moreover, it was found that there is only little difference (around 2% w/w) between the critical amounts of poly(ethylene oxide) needed for the ψ-condensation of linear DNA and supercoiled plasmid DNA over a wide range of salt concentrations [79], while a substantially larger difference could reasonably have been expected if supercoiled DNA were significantly compacted compared to linear DNA.…”
Section: A -Supercoilingmentioning
confidence: 99%